Age-dependent alterations of Fcγ receptor-mediated effector functions of human polymorphonuclear leucocytes - FULOP, T. JR; FORIS, G; WORUM, I; LEOVEY, A (Clinical and experimental immunology, 1985)
Changes in the effector functions in polymorphonuclear leucocytes (PMNL), harvested from blood of young and aged healthy subjects of both sexes, were studied. FC gamma-receptor (Fc gamma R)-mediated incorporation of IgG coated 51Cr-HRBC significantly increased in the aged male group, while the phagocytosis of pre-opsonized fungi (Saccharomyces cerevisiae and Candida albicans) was independent of both the age and sex. However, the intracellular killing capacity of neutrophils obtained from aged male subjects significantly decreased toward 51Cr-labelled c. albicans. The antibody-dependent cellular cytotoxicity (ADCC) was also impaired with ageing in both sexes. The age-dependent decrease in the effector functions of PMNL may be explained, among others, by the fact that during yeast cell incorporation the increased cAMP level does not return to the basic level in the old group. On the other hand, the cGMP level which increased in PMNL of aged subjects does not show any progressive increase as in the young subjects, but remains unchanged. The oxidative metabolism producing free radicals being necessary for the effective intracellular killing and ADCC diminished in PMNL of aged subjects of both sexes. The above findings indicate that the adaptation of cyclic nucleotide system and the oxidative burst to the cell activation becomes impaired with ageing.